Simulation Analysis of the Reinforced Earthquake Resistance of RC Building Structure Model with Glass Fiber Reinforced Polymer Using Column Section Enlargement - Ketsri, Pichet; Leeanansaksiri, Anuchat; Srichandum, Sakchai; Nanthasan, Rangsi (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2025)
This research aimed to study earthquake resistance model of reinforced concrete building structure strengthened with Glass Fiber Reinforced Polymer (GFRP) by using column section enlargement. The building used in the study was a 4-storey reinforced concrete school building under the Ministry of Education, which was not designed to earthquake resistance. The behavior of the reinforced concrete school building was simulated before and after strengthening with GFRP compared with deformed bars to evaluate capacity of reinforced concrete structure using Nonlinear Static. The study results were found that the capacity level of bare reinforced concrete school building frame (BF) caused failure at the plastic hinge point of reinforced concrete columns on the 2nd to 4th floors of school building, which had behavior of strong beams and weak columns and had more Demand-Capacity Ratio (DCR) value than 1, which could not earthquake resistance. However, when the school building was strengthened with GFRP and deformed bars, it had a capacity to resist at 1.75 and 1.73 times, respectively, comparing to bare reinforced concrete school building frame (BF), and having Demand-Capacity Ratio (DCR) value of reinforcement with GFRP and reinforced with deformed bars with lower value than 1. Therefore, the reinforcement with GFRP was an alternative that could be used to replace deformed bars in earthquake resistance effectively.